HUBUNGAN PENGETAHUAN TENTANG KESEHATAN REPRODUKSI TERHADAP SIKAP MENGHADAPI SINDROM PRE-MENSTRUASI PADA REMAJA PUTRI SISWI X DAN XI MAN 2 MADIUN - Anggariksa, Ekki Dita; Ichsan, Burhannudin; Nirlawati, Dewi (Universitas Muhamadiyah Surakarta, 2013)
Approximately 1 billion people or 1 out of every 6 people in the world are teenagers, where 85% of them live in developing countries. The knowledge of adolescents about reproduction health in Indonesias still very low. Adolescent reproduction problems not only give impact physically but also can affect mental health, emotion, economical condition and social welfare in long term. Pre menstrual syndrome often leads to physical and emotional disorders. The objective of this research is to know the correlation of reproduction health knowledge toward the attitude to face pre-menstrual syndrome of female students on X and XI grade in MAN 2 Madiun. The study was cross sectional using cluster sampling. As much as 32 respondents (62%) had higher reproduction knowledge compared to the mean. 27 respondents (54%) had higher values above the average of attitude values . Data analysis of the Pearson test (p = 0.000), which is statistically signi? cant and r =0,740 indicates strong correlation. There was a signi? cant correlation between reproductive health knowledge toward attitude to face pre-menstrual syndrome of female students in X and XI grade in MAN 2 Madiun.Keywords: knowledge, reproductive health, attitude, pre-menstrual syndrome.